About romance without love and love without romance - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность", 2018)
In this article understanding phenomena of love is analyzed. There is described historical analysis of conception of love, which is reducing to two possible versions based on authenticity of feeling and the necessity of comfortable live. The evaluation of authenticity is based on the existential theory of truth, proposed by S. Kierkegaard